2004
DOI: 10.5551/jat.11.173
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Abdominal Fat Mass Assessed by Helical or Conventional Computed Tomography to Serum Leptin Concentration

Abstract: In the present study, we focused on the relationship of intra-abdominal visceral fat (VF) or subcutaneous fat (SF) mass to serum leptin levels, and also on the relationship of leptin to serum lipid and lipoprotein concentration. Subjects with obesity (26 men, 26 women) were recruited for this study. We obtained helical CT scans with a tube current of 150 mA, voltage of 120 kV and 2:1 pitch (table speed in relation to slice thickness), starting at the upper edge of the liver and continuing to the pelvis. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…Leptin concentrations have been reported to be associated with BMI and body fat (Ryan and Elahi 1996). Furthermore, Kobayashi et al (2004) showed the relationship between intraabdominal visceral fat mass by CT and serum leptin. Thus, our findings may reveal that hypoxic training is useful in the prevention of MS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Leptin concentrations have been reported to be associated with BMI and body fat (Ryan and Elahi 1996). Furthermore, Kobayashi et al (2004) showed the relationship between intraabdominal visceral fat mass by CT and serum leptin. Thus, our findings may reveal that hypoxic training is useful in the prevention of MS.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Kobayashi et al. () showed the relationship between intraabdominal visceral fat mass by CT and serum leptin. Thus, our findings may reveal that hypoxic training is useful in the prevention of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is an anorexigenic metabolic hormone that is secreted in proportion to fat mass [23] and decreases bone formation [24]. A strong positive correlation between fat mass and serum leptin concentrations has been reported [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Leptin's anti-osteogenic action was demonstrated by intracerebroventricular injection of leptin into an ob/ob mouse, which decreased bone formation (19). A strong positive correlation between fat mass and serum lipid concentrations has been reported (20). Studies have shown that hyperlipidemia may contribute to osteoporosis by increasing osteoclastic bone resorption (21) and osteoclast viability (22).…”
Section: Introductionmentioning
confidence: 99%